2022
DOI: 10.3389/fimmu.2022.934264
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the AIM2 Receptor in Circulating Cells of Post-COVID-19 Patients With Signs of Lung Fibrosis Is Associated With the Release of IL-1α, IFN-α and TGF-β

Abstract: Severe acute respiratory syndrome-coronavirus-2 (SARS‐CoV‐2), responsible for COVID-19, has caused a global pandemic. Observational studies revealed a condition, herein called as Long-COVID syndrome (PC), that affects both moderately and severely infected patients, reducing quality-of-life. The mechanism/s underlying the onset of fibrotic-like changes in PC are still not well defined. The goal of this study was to understand the involvement of the Absent in melanoma-2 (AIM2) inflammasome in PC-associated lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Together, these studies provide clinical and mechanistic evidence that the NLRP3 inflammasome is suppressed at the early stages of SARS-CoV-2 infection and overactivated at later stages, and this could be the main cause of the cytokine storm seen in severe COVID-19 patients. The later hyperactivation of the inflammasome could also help explain its harmful involvement in the long-COVID syndrome, as it has been reported that monocytes from patients with long-COVID syndrome display increased AIM2 inflammasome expression and responsiveness, and this was associated with lung fibrosis and worse respiratory symptoms [82].…”
Section: Coronavirusmentioning
confidence: 99%
“…Together, these studies provide clinical and mechanistic evidence that the NLRP3 inflammasome is suppressed at the early stages of SARS-CoV-2 infection and overactivated at later stages, and this could be the main cause of the cytokine storm seen in severe COVID-19 patients. The later hyperactivation of the inflammasome could also help explain its harmful involvement in the long-COVID syndrome, as it has been reported that monocytes from patients with long-COVID syndrome display increased AIM2 inflammasome expression and responsiveness, and this was associated with lung fibrosis and worse respiratory symptoms [82].…”
Section: Coronavirusmentioning
confidence: 99%
“…Indeed, considerable levels of AIM-2 were detected in monocytes infected by SARS-CoV-2 (Junqueira et al, 2021). Furthermore, AIM-2 receptor activation was observed in peripheral blood mononuclear cells (PBMCs) from post-Covid-19 patients that presented lung injuries (Colarusso et al, 2022). It was speculated that the ability of SARS-CoV-2 to induce AIM2 inflammasome response is due to the presence of cell free DNA (cfDNA) in several tissues of COVID-19 patient including lungs.…”
Section: Absent In Melanoma 2 Inflammasomementioning
confidence: 99%
“…16 Colarusso et al showed that AIM2 could trigger inflammation and programmed cell death by processing interleukin IL-1, IL-18, and pro-caspase 1 and activating them. 33 Other research found a potent correlation between inflammasome-mediated inflammation and Gradermin D in severe COVID-19 cases as opposed to those with milder symptoms. They also proposed that this could be attributed to the high production of AIM2 and highlighted in the immunopathogenesis of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 97%